EXAMINING THE TRENDS IN BANK DEPOSITS THROUGH INTERNAL AND EXTERNAL FACTORS BASED ON THE SUPPLY CHAIN STRATEGIES: A PRIMARY AND SECONDARY DATA SURVEY - Bakashbayev, Azatbek; Nurgaliyeva, Aliya; Gumar, Nazira; Khamidullina, Zhanat; Saduakassova, Markhabat (International Journal of Supply Chain Management, 2020)
Abstract- The banking sector is the basis of the economy of any country which relies on the supply chain strategies. Funding plays a significant role in the activities of banks, in the structure of which deposits to this day remain the cheapest and most significant resources. Bank deposits are also a major part of the country's savings. The level of bank deposits allows us to judge the quality of funding of second-tier banks. The level of attracting deposits is influenced by many external and internal factors of an economic, political, social nature. An analysis of the studies available in the economic literature shows either a one-sided study of factors affecting bank deposits and the use of mainly linear regression, or a study of factors on deposits of the country's banking sector as a whole. However, this approach does not allow us to see the degree of dependence of the level of deposits on various factors for individual banks, which is much more important when evaluating funding. The author presents an attempt to analyze the influence of external and internal factors on the level of the deposit base of individual second-tier banks in Kazakhstan using ridge regression and ANOVA. In addition, our study has provided the primary data analyses, covering the impact of supply chain management and green supply chain adoption on the banking sector deposits. It is found that some factors of supply chain management and green supply chain adoption are positively impacting on bank?s deposit while others are found to be non-significant determinants for predicting the deposits of the banks. However, supply chain management (6th item) is adversely impacting on the first and second measure of bank?s deposit. Similar trend is observed by green supply chain adoption (5th item) on first and third measure of bank?s deposits in Kazakhstan.